Palladium-catalysed cyclisation of alkenols: Synthesis of oxaheterocycles as core intermediates of natural compounds - Palík, Miroslav; Kožíšek, Jozef; Koóš, Peter; Gracza, Tibor (Beilstein Journal of Organic Chemistry, 2014)
The study of Pd-catalysed cyclisation reactions of alkenols using different catalytic systems is reported. These transformations affect the stereoselective construction of mono- and/or bicyclic oxaheterocyclic derivatives depending on a starting alkenol. The substrate scope and proposed mechanism of Pd-catalysed cyclisation reactions are also discussed. Moreover, the diastereoselective Pd-catalysed cyclisation of appropriate alkenols to tetrahydrofurans and subsequent cyclisation provided properly substituted 2,5-dioxabicyclo[2.2.1]heptane and 2,6-dioxabicyclo[3.2.1]octane, respectively. Such bicyclic ring subunits are found in many natural products including ocellenynes and aurovertines.
Keywords: alkenols; cycloetherification; homogeneous catalysis; natural products; palladium